ChemInform Abstract: Direct Nucleophilic Difluoromethylation of Enolizable Ketones with CHF2TMS/HMPA. Issue 25 (June 2016) - Michurin, Oleg M.; Radchenko, Dmytro S.; Komarov, Igor V.
Abstract: A novel protocol for the direct difluoromethylation of enolizable ketones is achieved with TmsCHF2 in the presence of CsF/HMPA as additives.